STUDIES ON SPREADING FACTORS : I. THE IMPORTANCE OF MECHANICAL FACTORS IN HYALURONIDASE ACTION IN SKIN - Hechter, Oscar (The Rockefeller University Press, 1947)
The spreading response induced by intradermal administration of hyaluronidase is influenced not only by enzyme concentration, but also by the volume and pressure of the injection. These pressure-volume factors influence the rate of spreading and determine the final area of spreading. When a constant volume is injected, the rate of spreading to the area determined by the volume of injection is a function of the enzyme concentration. These and other findings have led to the conclusion that hyaluronidase is an effective spreading agent only when the slow diffusion of enzyme in skin is accelerated by a localized increase of interstitial pressure and volume. These considerations of hyaluronidase action in skin have been utilized to explain the shape of the dosage-response curve of hyaluronidase spreading activity, and the differences in the spreading reactions between crude snake venoms and purified hyaluronidase. The significance of the findings as related to the rôle of hyaluronidase in bacterial invasiveness, and in the assay of S. F. are briefly discussed.